Letting the Brain Speak for Itself - Werner, Gerhard (Frontiers in Physiology, 2011)
Metaphors of Computation and Information tended to detract attention from the intrinsic modes of neural system functions, uncontaminated by the observer’s role in collection and interpretation of experimental data. Recognizing the self-referential mode of function, and the propensity for self-organization to critical states requires a fundamentally new orientation, based on Complex System Dynamics as non-ergodic, non-stationary processes with inverse power-law statistical distributions. Accordingly, local cooperative processes, intrinsic to neural structures and of fractal nature, call for applying Fractional Calculus and models of Random Walks with long-term memory in Theoretical Neuroscience studies.